Dynamic tuning of optical absorbers for accelerated solar-thermal energy storage. Issue 1 (December 2017) - Wang, Zhongyong; Tong, Zhen; Ye, Qinxian; Hu, Hang; Nie, Xiao; Yan, Chen; Shang, Wen; Song, Chengyi; Wu, Jianbo; Wang, Jun; Bao, Hua; Tao, Peng; et al.
Abstract Currently, solar-thermal energy storage within phase-change materials relies on adding high thermal-conductivity fillers to improve the thermal-diffusion-based charging rate, which often leads to limited enhancement of charging speed and sacrificed energy storage capacity. Here we report the exploration of a magnetically enhanced photon-transport-based charging approach, which enables the dynamic tuning of the distribution of optical absorbers dispersed within phase-change materials, to simultaneously achieve fast charging rates, large phase-change enthalpy, and high solar-thermal energy conversion efficiency. Compared with conventional thermal charging, the optical charging strategy improves the charging rate by more than 270% and triples the amount of overall stored thermal energy. This superior performance results from the distinct step-by-step photon-transport charging mechanism and the increased latent heat storage through magnetic manipulation of the dynamic distribution of optical absorbers. Solar-thermal energy storage based on phase-change materials suffers from slow thermal-diffusion-based charging. Here the authors alleviate this issue by introducing optical absorbers and controlling their distribution to accelerate charging process and thus improve solar-thermal energy conversion.